Functionalized supported membranes for quantifying adhesion of P. falciparum-infected erythrocytes - Fröhlich, Benjamin; Dasanna, Anil K.; Lansche, Christine; Czajor, Julian; Sanchez, Cecilia P.; Cyrklaff, Marek; Yamamoto, Akihisa; Craig, Alister; Schwarz, Ulrich S.; Lanzer, Michael; Tanaka, Motomu (Biophysical journal, 2021)
The pathology of Plasmodium falciparum malaria is largely defined by the cytoadhesion of infected erythrocytes to the microvascular endothelial lining. The complexity of the endothelial surface and the large range of interactions available for the infected erythrocyte via parasite-encoded adhesins make analysis of critical contributions during cytoadherence challenging to define. Here, we have explored supported membranes functionalized with two important adhesion receptors, ICAM1 or CD36, as a quantitative biomimetic surface to help understand the processes involved in cytoadherence. Parasitized erythrocytes bound to the receptor-functionalized membranes with high efficiency and selectivity under both static and flow conditions, with infected wild-type erythrocytes displaying a higher binding capacity than do parasitized heterozygous sickle cells. We further show that the binding efficiency decreased with increasing intermolecular receptor distance and that the cell-surface contacts were highly dynamic and increased with rising wall shear stress as the cell underwent a shape transition. Computer simulations using a deformable cell model explained the wall-shear-stress-induced dynamic changes in cell shape and contact area via the specific physical properties of erythrocytes, the density of adhesins presenting knobs, and the lateral movement of receptors in the supported membrane.
Gesehen am 05.11.2021